Exploring the relationship between carbon dioxide emissions, urbanisation and financial deepening for Turkey using the symmetric and asymmetric causality approaches - Faisal, Faisal; Pervaiz, Ruqiya; Ozatac, Nesrin; Tursoy, Turgut (Springer, 2021)
This paper investigates the association among carbon dioxide emissions, electricity consumption, capital, financial deepening and urbanisation using data from 1968 to 2013 collected from the World Bank for Turkey. Further, this study applies single- and bi-endogenous structural break unit root approach in addition to the Ng and Perron (2001) to explore the integration order of the series. The bounds test is adopted to analyse the long-run connection among the variables. The robustness of the bounds test was further investigated using the Bayer-Hanck (Bayer and Hanck, Journal of Time Series Analysis 34:83-95, 2013) combined cointegration method. The long-run effects identified the evidence of an inverted U-shaped association among carbon dioxide and urbanisation. This suggests that rapid urbanisation increases the levels of pollution in the initial stages of development. However, after reaching a threshold point, urbanisation reduces environmental pollution. Financial development, electricity use and capital affect COE significantly and positively in both the short and long run, while GDP has a positive and insignificant effect. Additionally, the causal relationships among the variables are identified using the symmetric and asymmetric causal techniques. The outcomes of the causal results showed that financial deepening, urbanisation and electricity use are causing environmental pollution in the short run in the symmetric causality, while CO2 is causing financial development based on the asymmetric causality. The findings suggest that green technologies should be adopted. Further, the use of renewable energy must be ensured for generating the electricity as it will facilitate a reduction in the COE.
Keywords: Asymmetric causality; Ecological modernisation (EM) theory; Financial deepening; Sustainable development; Urbanisation